Mebendazolium mesylate anhydride salt: rational design based on supramolecular assembly, synthesis, and solid-state characterization - Gutiérrez, Eduardo Luciano (2024)
The design mebendazole (MBZ) multicomponent systems is important to obtain new materials that incorporate the API (active pharmaceutical ingredient) with better thermal stability, avoiding the interconversion of desmotropes. Interestingly, the presence of water molecules in the mebendazolium mesylate monohydrate prevents the formation of the R22(8) supramolecular synthon, found in all mebendazolium salts with polyatomic counterions. Here, we designed a new mebendazolium mesylate anhydrous salt based on statistical scrutiny of all mebendazole crystal structures identified in the literature and an exhaustive analysis of the conformational and geometrical requirements for the supramolecular assembly. The synthesis of this new salt and its solid-state characterization through single-crystal X-ray diffraction and complementary techniques are presented. As expected, mebendazole recrystallization in methanol with methanesulfonic acid - a Food and Drug Administration accepted coformer - in the absence of water yields a mesylate anhydrous salt with 1 : 1 stoichiometry. This new salt crystallizes in the P212121 (19) space group. The main intermolecular interactions found in the crystal structure are the hydrogen bonds that form a R22(8) supramolecular motif that assembles the ionic pairs. Additional non-classical H-bond, as well as π⋯π and carbonyl⋯cation interactions, contribute to the final stabilization of the crystal packing. This new salt is stable up to 205 °C when it undergoes the endothermic loss of the ester moiety to yield 2-amino-5-benzoylbenzimidazole. Moreover, preliminary dissolution experiments in aqueous 0.1 mol L−1 HCl suggest an apparent solubility of mebendazolium mesylate anhydride 2.67 times higher than that of the preferred for pharmaceutical formulations MBZ form C.